Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

List the potential solutions to [tex]$2 \log x - \log 3 = \log 3$[/tex] from least to greatest.

[tex]x = \square[/tex] or [tex]x = \square[/tex]


Sagot :

To solve the equation [tex]\( 2 \log x - \log 3 = \log 3 \)[/tex], we proceed as follows:

1. Isolate the logarithmic term involving [tex]\( x \)[/tex]:
[tex]\[ 2 \log x - \log 3 = \log 3 \][/tex]

2. Solve for [tex]\( 2 \log x \)[/tex] by adding [tex]\( \log 3 \)[/tex] to both sides of the equation:
[tex]\[ 2 \log x = \log 3 + \log 3 \][/tex]

3. Combine the logarithms on the right-hand side using the property [tex]\(\log a + \log b = \log(a \cdot b)\)[/tex]:
[tex]\[ 2 \log x = \log(3 \cdot 3) \][/tex]
[tex]\[ 2 \log x = \log 9 \][/tex]

4. Divide both sides by 2 to solve for [tex]\( \log x \)[/tex]:
[tex]\[ \log x = \log 9 / 2 \][/tex]
[tex]\[ \log x = \log 9^{1/2} \][/tex]

5. Simplify the right-hand side to get [tex]\( x \)[/tex]:
[tex]\[ \log x = \log 3 \][/tex]

6. Since the logarithm is the same on both sides, we equate the arguments:
[tex]\[ x = 3 \][/tex]

So, the solution to the equation [tex]\( 2 \log x - \log 3 = \log 3 \)[/tex] is [tex]\( x = 3 \)[/tex].

Thus, listing the potential solutions from least to greatest:
[tex]\[ x = 3 \][/tex]

DONE
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.